2021
DOI: 10.1021/acsenergylett.1c01380
|View full text |Cite
|
Sign up to set email alerts
|

Narrow-Band Violet-Light-Emitting Diodes Based on Stable Cesium Lead Chloride Perovskite Nanocrystals

Abstract: CsPbCl3 nanocrystals are potential ultrapure emitters. But it is challenging to synthesize CsPbCl3 nanocrystals with sufficient stability, which impedes their application in light-emitting devices. In this work, we report a facile phosphoryl-chemistry-mediated synthesis approach to synthesizing stable CsPbCl3 nanocrystals, in which the phenylphosphonic dichloride (PhPOCl2) precursor is employed. In addition to the high reactivity of the P–Cl bond of PhPOCl2 for providing adequate Cl, the derived P=O with good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
54
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 83 publications
1
54
0
Order By: Relevance
“…For optoelectronic device applications, appropriate purification steps are necessary to remove the excess insulating organic ligands of PQDs with the assistance of anti-solvents, which yet often deteriorate the optical properties of PQDs. 40 With this in mind, we then purified PQDs repeatedly with ethyl acetate as the anti-solvent. It was found that small PQDs converted into perovskite nanosheets (PNSs) with various lateral sizes after five cycles of purification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For optoelectronic device applications, appropriate purification steps are necessary to remove the excess insulating organic ligands of PQDs with the assistance of anti-solvents, which yet often deteriorate the optical properties of PQDs. 40 With this in mind, we then purified PQDs repeatedly with ethyl acetate as the anti-solvent. It was found that small PQDs converted into perovskite nanosheets (PNSs) with various lateral sizes after five cycles of purification (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8,9,25,32,33 The extremely narrow emission with FWHM of ∼ 10 nm of excitonic emission is a record value for CsPbCl 3 NCs, which can be attributed to the intrinsic advantage of the anion injection method. 4,14,16 As shown in Figure 3B, the optical properties of Mn 2+ -doped CsPbCl 3 NCs are highly dependent on the OAm-Cl content. In particular, the total PL QYs increases firstly, reaching a maximum value of 56% for S5 with OAm-Cl of 1.0 mL, and then slightly decreases with further increasing OAm-Cl content (Figure 3C).…”
Section: Resultsmentioning
confidence: 95%
“…The emission band centered at ∼ 410 nm with the full width at half‐maximum (FWHM) of ∼ 10 nm can be assigned to the excitonic recombination of CsPbCl 3 host and the broad band orange emission with FWHM of ∼ 78 nm originates from 4 T 1 → 6 A 1 transition of the doped Mn 2+ ions, respectively 8,9,25,32,33 . The extremely narrow emission with FWHM of ∼ 10 nm of excitonic emission is a record value for CsPbCl 3 NCs, which can be attributed to the intrinsic advantage of the anion injection method 4,14,16 . As shown in Figure 3B, the optical properties of Mn 2+ ‐doped CsPbCl 3 NCs are highly dependent on the OAm‐Cl content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations